Realizing the Potential of Genomics across the Continuum of Precision Health Care: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
The National Academies Roundtable on Genomics and Precision Health, in collaboration with the National Cancer Policy Forum, hosted a public workshop that examined how genomic data are used in health care, outside of the traditional settings for clinical genetics. The workshop identified opportunities for advancement of precision health care delivery. The event also explored how patients, clinicians, and payers assess and act upon the risks and benefits of genomic screening and diagnostic testing. Discussions focused on strategies to ensure that genomic applications are responsibly and equitably adopted to benefit populations as well as individuals over time. This Proceedings of a Workshop summarizes content from the event.
Keywords: Health and Medicine

Using Population Descriptors in Genetics and Genomics Research: A New Framework for an Evolving Field - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
Genetic and genomic information has become far more accessible, and research using human genetic data has grown exponentially over the past decade. Genetics and genomics research is now being conducted by a wide range of investigators across disciplines, who often use population descriptors inconsistently and/or inappropriately to capture the complex patterns of continuous human genetic variation. In response to a request from the National Institutes of Health, the National Academies assembled an interdisciplinary committee of expert volunteers to conduct a study to review and assess existing methodologies, benefits, and challenges in using race, ethnicity, ancestry, and other population descriptors in genomics research. The resulting report focuses on understanding the current use of population descriptors in genomics research, examining best practices for researchers, and identifying processes for adopting best practices within the biomedical and scientific communities.
Keywords: Health and Medicine; Behavioral and Social Sciences

Human Genome Editing: Science, Ethics, and Governance - National Academy of Sciences; National Academy of Medicine; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
Genome editing is a powerful new tool for making precise alterations to an organism's genetic material. Recent scientific advances have made genome editing more efficient, precise, and flexible than ever before. These advances have spurred an explosion of interest from around the globe in the possible ways in which genome editing can improve human health. The speed at which these technologies are being developed and applied has led many policymakers and stakeholders to express concern about whether appropriate systems are in place to govern these technologies and how and when the public should be engaged in these decisions.
Keywords: Health and Medicine

Genome-Based Diagnostics: Demonstrating Clinical Utility in Oncology: Workshop Summary - Institute of Medicine (The National Academies Press, 2013)
Genome-Based Diagnostics: Demonstrating Clinical Utility in Oncology is the summary of a workshop convened in May 2012 by the Roundtable on Translating Genomic-Based Research for Health and the Center for Medical Technology Policy of the Institute of Medicine to foster the identified need for further sustained dialogue between stakeholders regarding the clinical utility of molecular diagnostics. The workshop brought together a wide range of stakeholders, including patients, health care providers, policy makers, payers, diagnostic test developers, researchers, and guideline developers, to identify the challenges and opportunities in advancing the development and use of molecular diagnostic tests designed to guide the treatment and management of patients with cancer. The sequencing of the human genome has greatly accelerated the process of linking specific genetic variants with disease. These findings have yielded a rapidly increasing number of molecular diagnostic tests designed to guide disease treatment and management. Many of these tests are aimed at determining the best treatments for specific forms of cancer, making oncology a valuable testing ground for the use of molecular diagnostic tests in medicine in general. Nevertheless, many questions surround the clinical value of molecular diagnostic tests, and their acceptance by clinicians, payers, and patients has been unpredictable. A major limiting factor for the use of these tests has been the lack of clear evidence of clinical utility. Genome-Based Diagnostics assesses the evidentiary requirements for clinical utility of molecular diagnostics used to guide treatment decisions for patients with cancer; discusses methodologies related to demonstrating these evidentiary requirements that meet the needs of all stakeholders; and considers innovative, sustainable research collaborations for generating evidence of clinical utility involving multiple stakeholders.
Keywords: Health and Medicine

Improving the Efficiency and Effectiveness of Genomic Science Translation: Workshop Summary - Institute of Medicine (The National Academies Press, 2014)
The process for translating basic science discoveries into clinical applications has historically involved a linear and lengthy progression from initial discovery to preclinical testing, regulatory evaluation and approval, and, finally, use in clinical practice. The low rate of translation from basic science to clinical application has been a source of frustration for many scientists, clinicians, investors, policy makers, and patients who hoped that investments in research would result in improved products and processes for patients. Some feel that the anticipated deliverables from the Human Genome Project have not yet materialized, and although understanding of human health and disease biology has increased, there has not been a concomitant increase in the number of approved drugs for patients over the past 10 years. Improving the Efficiency and Effectiveness of Genomic Science Translation is the summary of a workshop convened by the Institute of Medicine Roundtable on Translating Genomic-Based Research for Health in December 2012 to explore ways to improve the efficiency and effectiveness of the translation of genomic science to clinical practice. The workshop convened academic researchers, industry representatives, policy makers, and patient advocates to explore obstacles to the translation of research findings to clinical practice and to identify opportunities to support improvement of the early stages of the process for translation of genetic discoveries. This report discusses the realignment of academic incentives, the detection of innovative ways to fund translational research, and the generation or identification of alternative models that accurately reflect human biology or disease to provide opportunities to work across sectors to advance the translation of genomic discoveries.
Keywords: Health and Medicine

Refining Processes for the Co-Development of Genome-Based Therapeutics and Companion Diagnostic Tests: Workshop Summary - Institute of Medicine (The National Academies Press, 2014)
Many drug developers have examined new strategies for creating efficiencies in their development processes, including the adoption of genomics-based approaches. Genomic data can identify new drug targets for both common and rare diseases, can predict which patients are likely to respond to a specific treatment, and has the potential to significantly reduce the cost of clinical trials by reducing the number of patients that must be enrolled in order to demonstrate safety and efficacy. A key component of the approval of targeted therapeutics is the ability to identify the population of patients who will benefit from treatment, and this has largely hinged on the co-development and co-submission to the FDA of a companion diagnostic test.The co-development process, or the development of the test and drug for the simultaneous submission to FDA, has led to a major alteration in the way that drugs are being developed, with traditionally separate entities—pharmaceutical and diagnostic companies—now working in close collaboration.
Keywords: Health and Medicine

The Science and Applications of Microbial Genomics: Workshop Summary - Institute of Medicine (The National Academies Press, 2013)
Over the past several decades, new scientific tools and approaches for detecting microbial species have dramatically enhanced our appreciation of the diversity and abundance of the microbiota and its dynamic interactions with the environments within which these microorganisms reside. The first bacterial genome was sequenced in 1995 and took more than 13 months of work to complete. Today, a microorganism's entire genome can be sequenced in a few days. Much as our view of the cosmos was forever altered in the 17th century with the invention of the telescope, these genomic technologies, and the observations derived from them, have fundamentally transformed our appreciation of the microbial world around us. On June 12 and 13, 2012, the Institute of Medicine's (IOM's) Forum on Microbial Threats convened a public workshop in Washington, DC, to discuss the scientific tools and approaches being used for detecting and characterizing microbial species, and the roles of microbial genomics and metagenomics to better understand the culturable and unculturable microbial world around us. Through invited presentations and discussions, participants examined the use of microbial genomics to explore the diversity, evolution, and adaptation of microorganisms in a wide variety of environments; the molecular mechanisms of disease emergence and epidemiology; and the ways that genomic technologies are being applied to disease outbreak trace back and microbial surveillance. Points that were emphasized by many participants included the need to develop robust standardized sampling protocols, the importance of having the appropriate metadata, data analysis and data management challenges, and information sharing in real time. The Science and Applications of Microbial Genomics summarizes this workshop.
Keywords: Biology and Life Sciences; Health and Medicine; Conflict and Security Issues

The Common Thread: A Story of Science, Politics, Ethics, and the Human Genome - Sulston, John; Ferry, Georgina (The National Academies Press, 2002)
The world was agog when scientists made the astounding announcement that they had successfully sequenced the human genome. Few contributed so directly to this feat as John Sulston. This is his personal account of one of the largest international scientific operations ever undertaken.
Keywords: Explore Science; Biography and Autobiography